Global burden of burns among children and adolescents: a trend analysis from the global burden of disease study 2019 - Hao Zhu; Hao Zhu; Ke Wang; Xiong Liu; Jianfeng Ji; Peng Yang; Feng Xu (Frontiers in Public Health)
PreciseThis study investigates global trends in burns among children and adolescents using data from the Global Burden of Disease Study 2019. Analyzing incidence and YLD rates across 204 countries from 1990 to 2019 reveals a general decline in burn-related injuries, with age and sex influencing trends. Notably, in high-SDI regions, incidence rates initially increased before reversing. These findings highlight the need for targeted public health policies and resource allocation to reduce burn-related risks in vulnerable populations.BackgroundGiven the lack of long-term trend studies on global burns among children and adolescents, this study examined trends in the global burden of burns among children and adolescents.MethodsThe Global Burden of Disease (GBD) Study 2019 provided the statistical data. Sex, age, region, and SDI were used as stratification variables in the study to evaluate the prevalence of burns injuries among kids and teenagers across 204 nations and territories between 1990 and 2019. YLD rates per 100,000 people and incidence rates together with their respective average annual percentage changes (AAPC) were computed to evaluate burden trends. Furthermore, AAPC in YLD rates and incidence rates spanning various age cohorts were analyzed using the Joinpoint software.ResultsThe worldwide burns incidence and YLD rates of burns among kids and teenagers exhibited a general declining trend between 1990 and 2019. Concerning the general trend in new cases, incidence rates, and YLD rates, age was positively associated. In 2019, the incidence rate for females surpassed that of males, while YLD rates for females were consistently higher than those of males. New Zealand, Czechia, and Australia rank as the top three among the 204 countries studied. Interestingly, in the high SDI range, the expected values based on incidence rates reversed after first rising with the SDI.ConclusionOverall, the incidence and YLD rates of burns among children and adolescents have declined globally, though significant disparities exist across age groups, sexes, regions, and countries. These findings could help guide the development of more targeted strategies to reduce the burn burden in this population.